The Role of the Sleman District Disaster Management Agency in Disaster Communication Regarding Mount Merapi in Sleman Regency, Yogyakarta - Nurjanah, Adhianty (International Publisher (YAPENBI), 2025)
Mount Merapi is one of the most active volcanoes in Indonesia and poses a serious threat to the people of Sleman, especially following the 2010 eruption that caused significant damage and loss of life. Although Indonesia has a developed disaster management system, effective disaster communication remains a challenge, particularly in delivering information that is timely, accurate, and easily understood by the public. This research aims to explore the role of the Regional Disaster Management Agency (BPBD) of Sleman Regency in disaster communication, specifically related to the mitigation and management of Mount Merapi disasters. The research method employs a qualitative descriptive approach, with data collection techniques conducted through in-depth interviews with the Head of BPBD and the Head of the BPBD Secretariat of Sleman Regency, as well as with the community and disaster awareness groups. The data analysis technique used is the Miles & Huberman Model, and data triangulation is performed to ensure data validity. The results of this study indicate that the BPBD of Sleman Regency plays a crucial role in disaster communication, both in mitigation and disaster management. Effective communication is supported by strategies for delivering accurate messages, using easily understandable language, ensuring accessibility and inclusivity, as well as collaboration and coordination with various stakeholders. This study recommends strengthening cross-sector coordination and enhancing community capacity to understand disaster information in order to improve preparedness for Mount Merapi disaster.